Study of the Effects on Turbocharger Performance Generated by the Presence of Foreign Objects at the Compressor Intake. Issue 2 (16th November 2011) - Serrano, J.R.; Tormos, B.; Gargar, K.L.; Bouffaud, F.
<x xml:space="preserve">Abstract</x> The study performed on this work consists of evaluating the consequences of the introduction of various foreign objects at the compressor inlet of a turbocharger. The most plausible objects were selected. A specific test bench was set up in order to perform the experiment and measure the compression ratio and compressor efficiency evolution. Measurements were performed before (healthy compressor) and after the object introduction (damaged compressor). Results obtained indicate that losses in performance can be very important, but also that the compressor can swallow hard objects without visible damage. Therefore, the experiments were filmed with a high speed camera. Visual information has helped to better understand the phenomenon, to explain the measurements, and it has been taken into account in order to perform final diagnosis. As expected, the harder the object is and the longer it hits compressor wheel before being swallowed, the most severe is the damage. Nevertheless, softer material can reach abnormal performance, but in randomly manner and such incipient damage can be detected easily in high air flow rates than in lower.